Bank accounts, bank concentration and mobile money innovations - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2023)
The present study investigates how increasing bank accounts and bank concentration affect mobile money innovations in 148 countries. It builds on scholarly and policy concerns in the literature that increasing bank accounts may not be having the desired effects on financial inclusion on the one hand and on the other, that bank concentration which is a proxy for market power is a relevant mobile money innovation demand factor. The empirical evidence is based on Tobit regressions. From the findings, it is apparent that boosting bank accounts is positively related to the three mobile money innovations (i.e. mobile bank accounts and the mobile phone used to send money). Moreover, some critical levels of bank account penetration require complementary policies in order to maintain the positive relationship between boosting bank accountsand positive outcomes in terms of money mobile innovations.Conversely,financial inclusion in terms of the three mobile money innovations is not significantly apparent upon enhancing bank concentration. Policy implications are discussed in the light of the provided thresholds for complementary policies.
Keywords: D10; D14; D31; D60; O30; 330; Mobile money; technology; diffusion; financial inclusion; inclusive innovation; information asymmetry